Green Synthesis of Activated Carbons from Coconut Coir Dust via Steam Activation for Supercapacitor Electrode Applications - Jirayu Kongtip; Natapol Kanjulkeat; Thanapol Ninneit; Norapat Phanapadipong; Nattapat Chaiammart; Apiluck Eiad‐ua; Ratiporn Munprom; Gasidit Panomsuwan (Chemistry, 2025)
Activated carbons derived from coconut coir dust were synthesized via a two-step process combining carbonization and steam activation for application as electrode materials in supercapacitors. The influence of carbonization temperature (500–700 °C) on the morphological, structural, textural, and electrochemical properties of the resulting activated carbons was systematically investigated. Increasing the carbonization temperature led to a progressive collapse of the cellular structure and formation of a more compact and thermally stable carbon matrix, while the overall morphology remained largely unchanged after steam activation. The steam-activated carbon prepared from the carbonized sample at 700 °C (SA-CCD-7) exhibited the highest specific surface area (889 m2 g−1) and a well-developed hierarchical micro–mesoporous structure. Structural analyses confirmed the amorphous nature and an increase in structural disorder after activation, consistent with the enhanced pore development. Electrochemical measurements in 6 M KOH using a three-electrode system revealed that the SA-CCD-7 displayed a typical electric double-layer capacitor (EDLC) behavior, delivering the highest specific capacitance of 86 F g−1 at 1 A g−1 and retaining 81% of its initial capacitance at 20 A g−1, demonstrating excellent rate capability. The symmetric coin-cell supercapacitor device assembled with SA-CCD-7 as the electrodes achieved an energy density of 0.9–1.2 Wh kg−1 and a power density of 50–2500 W kg−1, along with remarkable cycling stability over 10,000 cycles with negligible capacitance loss. These findings highlight steam activation of coconut coir dust as a simple, scalable, and eco-friendly approach for producing biomass-derived carbon electrodes for sustainable energy storage applications.
Keywords: Supercapacitor Materials and Fabrication; Adsorption and biosorption for pollutant removal; Aerogels and thermal insulation